Planejamento de transporte urbano: estudo de caso da linha verde em Curitiba - Sanches, Alexandre Milkiewicz (2008)
Regardless the size of the city, the planning of a passenger bus transport system involves many variables. Not only cleaning, comfort and punctuality are important basic things when it comes to the quality of the service but also the choice of the vehicle that should meet the different customer demands. Big cities depend on a more careful planning so that transportation becomes more accessible to their citizens. However, this is not the case of passenger means of transportation which, most of time, are constantly crowded and do not live up to people’s expectations. Apart from this, vehicles are badly kept and emit pollutants, which impact the environment negatively. The objective of this research was to find out what people in charge of passenger means of transportation do when it comes to planning and its effect on: service quality, quality of vehicles, economic, environmental and social aspects. The question addressed was the relevant criteria taken into account when the planning of passenger transport. The hypotheses put forward were: the bus is the means of transportation most used in the country and if managers are to become the system attractive to the customer and contribute to the city traffic, they must face a great responsibility. The scope of this case study is the managers responsible for the planning of transport in the city of Curitiba, State of Paraná, which has been internationally acknowledged for its outstanding passenger transport system whose primarily intention is to improve its system in order to satisfy the existing and future demands. The general objective of this work was to study the competitive differentials of the passenger transport for the Curitiba City such as the project named “Linha Verde” (Green Line in English). The importance of a more detailed study such as this can be explained by the problems which are either brought about by the lack of planning in the cities or by the variables concerning specially buses. Being an issue that concerns Production Engineering and its relevance in the present day, an optimization of these management abilities about transport aims at encompassing strategic and operational planning as well as techniques and tools that are locally adapted to the profile of the managers and the city characteristics. By getting examples from other cities that tried alternative ways and looking at the results they obtained, we answer the question about the challenges of running a passenger transport in this day and age. The results show that planning is still the only way to organize a city, especially when it comes to mobility, and promoting a good quality passenger transport is the way to go.